Effect of topical atropine on astigmatism. Issue 6 (11th February 2009) - Chia, A; Chua, W-H; Tan, D
Abstract : Aim: The aim of this study was to determine if topical atropine, used to retard axial length elongation and myopia progression, had any effect on ocular astigmatism. Methods: Data collected from subjects enrolled in the Atropine in the Treatment of Myopia (ATOM) study were analysed. In this study, 400 myopic children (aged 6–12 years) were randomly assigned to administer atropine 1% or a placebo daily to a randomly selected eye for 2 years. Cycloplegic autorefraction and keratomy readings were measured using a Canon RK5 autorefractor. The refractive error was then split into its power vector components: J0 and J45. Results: Astigmatism increased by 0.12–0.16 D per year in both treated and placebo groups. There was no difference between groups (p = 0.182). The increase was mirrored by an increase in corneal astigmatism of 0.10–0.13 D per year, suggesting that most of the change was corneal in nature. There was an increase in J0 vector (with-the-rule astigmatism) with no change in the J45 (oblique) vector over time. The change in the J0 vector was significantly larger in the atropine-treated versus atropine-untreated eyes during the 2-year treatment period (p = 0.011), but this difference disappeared after atropine was stopped. Conclusion: The use of atropine on a daily basis over 2 years did not have any clinically significant effect on astigmatism.